Women’s Disempowered Behavior as an Impact of Over-ruling Government as Reflected in Collins’ The Hunger Games (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2018)
This study aims at explaining the over-ruling government in society results women’s disempowered behavior as reflected in Collins’ The Hunger Games which compared to the historical and social condition happening in the American society. This study is a qualitative analysis by applying a Carol Gilligan’s approach, especially in care-focused feminism. The data were collected by reading, identifying, interpreting and analyzed using the approach and theories which used in this study by relating to binary opposition, social and historical events and society belief in seeing women in the real life where the author produced the novel. The results of this study were the explanation of how government’s rules affect and result women disempowered behavior which begins with the internal conflict that women felt when the way society around them expect women to act and behave in some certain ways which was not parallel with some government’s rules. The government’s rules indirectly demand women to act and behave in some certain ways outside the way society expect women to act and behave when the rules were made without considering women’s position in society.